A new species of Stephonyx (Amphipoda, Amphilochida, Lysianassoidea) from Brazil - Sorrentino, Rayane; Souza-Filho, Jesser F.; Senna, André R. (Zootaxa, 2018)
A new species of Stephonyx Lowry and Stoddart, 1989 from northeastern Brazil is described, the second record of the genus from Brazil. The new Brazilian species is morphologically close to the type species of the genus. In this paper we compare the different descriptions of Stephonyx biscayensis (Chevreux, 1908) and recommend the necessity of a revision, since some described species may or may not be S. biscayensis.